Mutations in Drosophila myb lead to centrosome amplification and genomic instability. - Fung, S.M.; Ramsay, G.; Katzen, A.L. (Development, 2002)
We have previously established that the single myb gene in Drosophila melanogaster, Dm myb, which is related to the proto-oncogene Myb, is required for the G2/M transition of the cell cycle and for suppression of endoreduplication in pupal wing cells. We now report that studies of the abdominal phenotype in loss-of-function Dm myb mutants reveal additional roles for Dm myb in the cell cycle, specifically in mitosis. Abdominal epidermal cells that are mutant for Dm myb proliferate more slowly than wild-type controls throughout pupation, with particularly sluggish progression through the early stages of mitosis. Abnormal mitoses associated with multiple functional centrosomes, unequal chromosome segregation, formation of micronuclei, and/or failure to complete cell division are common in the later cell cycles of mutant cells. Resulting nuclei are often aneuploid and/or polyploid. Similar defects have also been observed in loss-of-function mutations of the tumor suppressor genes p53, Brca1 and Brca2. These data demonstrate that in abdominal epidermal cells, Dm myb is required to sustain the appropriate rate of proliferation, to suppress formation of supernumerary centrosomes, and to maintain genomic integrity.